Battery current collector, battery electrode, method for producing battery current collector, and method for peeling battery current collector
By using a dispersed crystalline resin or a basecoat layer of a mixture of resin and carbon particles in a lithium-ion battery and heating above the melting point of the crystalline resin, the problem of difficulty in peeling the electrode active material layer in a lithium-ion battery is solved, and the cost is reduced And improve efficiency.
Patent Information
- Application Number
- CN202410800655.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-16
- Filing Date
- 2024-06-20
- Publication Date
- 2024-12-31
AI Technical Summary
The ultrasonic treatment methods in existing lithium-ion batteries have problems of liquid management difficulties and high cost, and the metal foil wears in the treatment liquid, which may lead to metal powder mixing and affect reuse efficiency.
Using a dispersed crystalline resin or a mixture of resin and carbon particles, the electrode active material layer is peeled off from the conductive layer by heating to a temperature above the melting point of the crystalline resin, thereby reducing costs and improving efficiency.
The easy peeling of the electrode active material layer is achieved, reducing the cost of useful components in reuse, and reducing the risk of peeling during the increase in internal resistance and charging and discharging.
Smart Images

Figure CN119230838A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a battery collector, a battery electrode, and a preparation method and a stripping method of the battery collector. Background Art
[0002] Lithium-ion batteries are used in a variety of applications due to their excellent properties such as high energy density and long life. The positive electrode of lithium-ion batteries usually contains rare metals such as cobalt, nickel, and manganese, and securing these mineral resources has become a problem. On the other hand, research is being conducted on methods to recover these rare metals from used lithium-ion batteries.
[0003] For example, there is known a method in which an electrode active material layer on a metal foil is irradiated with ultrasonic waves in a liquid tank to break the positive electrode active material layer and remove it from the metal foil (for example, see Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2023-511520 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, the ultrasonic irradiation method requires management of the treatment liquid and has high treatment costs. In addition, the metal foil may be worn in the treatment liquid, and metal powder may be mixed in the treatment liquid.
[0009] The present invention has been made in view of such circumstances, and provides a battery current collector in which an electrode active material layer can be easily peeled off from a conductor layer.
[0010] Means of solving the problem
[0011] The present invention provides a battery current collector, characterized in that it comprises a conductor layer and an undercoat layer provided on the conductor layer, wherein the undercoat layer is a layer of a dispersed crystalline resin or a mixture layer of a crystalline resin and carbon particles, and when the undercoat layer is a layer of the dispersed crystalline resin, the conductor layer is exposed in the gaps of the crystalline resin contained in the undercoat layer, and when the undercoat layer is a mixture layer of the crystalline resin and carbon particles, the mass of the undercoat layer per unit area is 0.1 g / m 2 Above and less than 10g / m 2 , the melting point of the crystalline resin contained in the primer layer is below 200°C.
[0012] The present invention also provides a battery electrode, which includes the current collector of the present invention and an electrode active material layer disposed on the undercoat layer.
[0013] The present invention also provides a method for preparing a collector for a battery, which comprises the following steps: applying a dispersion containing crystalline resin particles dispersed in a dispersion medium containing a water-soluble organic compound or a liquid organic compound and water onto a conductive layer, and drying the coating film to form a primer layer.
[0014] The present invention also provides a stripping method, which is a stripping method for stripping an electrode active material layer contained in an electrode from a conductor layer, wherein the electrode comprises a current collector and an electrode active material layer, the current collector comprises a conductor layer and an undercoat layer disposed on the conductor layer, and the electrode active material layer is disposed on the undercoat layer. The undercoat layer is a layer of dispersed crystalline resin or a mixture layer of crystalline resin and carbon particles, the melting point of the crystalline resin contained in the undercoat layer is below 200°C, and the stripping method comprises a stripping step, wherein at least a portion of the undercoat layer is heated to a temperature above the melting point of the crystalline resin to strip the electrode active material layer from the conductor layer.
[0015] Effects of the Invention
[0016] By heating at least a portion of the primer layer contained in the battery electrode using the battery collector of the present invention to a temperature above its melting point, the crystalline resin can be melted and the electrode active material layer can be easily peeled off from the conductor layer. Therefore, the cost of reusing the useful components contained in the electrode active material layer or the collector can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 (a) Figure 1 (b) are schematic cross-sectional views of battery current collectors according to one embodiment of the present invention.
[0018] Figure 2 (a) Figure 2 (b) are schematic cross-sectional views of battery electrodes according to one embodiment of the present invention.
[0019] Figure 3 This is a SEM photograph of the cross section of the positive electrode for the battery after heat treatment.
[0020] Description of Reference Numerals
[0021] 2: Conductor layer 3: Primer layer 4: Crystalline resin particles
[0022] 5: Electrode active material layer 10: Battery current collector 20: Battery electrode DETAILED DESCRIPTION
[0023] Hereinafter, a plurality of embodiments of the present invention will be described using the drawings. The configurations shown in the drawings and the following description are exemplary, and the scope of the present invention is not limited to the configurations shown in the drawings and the following description.
[0024] First embodiment
[0025] Figure 1 (a) is a schematic cross-sectional view of a battery current collector according to this embodiment, Figure 2 (a) is a schematic cross-sectional view of the battery electrode according to this embodiment.
[0026] The battery collector 10 of this embodiment comprises a conductor layer 2 and a primer layer 3 arranged on the conductor layer 2, wherein the primer layer 3 is a layer of dispersed crystalline resin, and the conductor layer 2 is exposed in the gaps of the crystalline resin contained in the primer layer 3, and the melting point of the crystalline resin contained in the primer layer 3 is below 200°C.
[0027] The battery electrode 20 of the present embodiment includes the battery current collector 10 of the present embodiment and the electrode active material layer 5 provided on the undercoat layer 3 .
[0028] The battery collector 10 is a collector for the electrode of the battery, and becomes a conductive path between the electrode active material layer 5 and the battery terminal. The battery is not particularly limited, and is preferably a lithium ion battery. In addition, the battery collector 10 can be a collector for the positive electrode of the battery, or a collector for the negative electrode of the battery. In addition, the battery collector 10 can also be a collector for collecting positive or negative charges of the electrode active material layer 5.
[0029] The conductor layer 2 is a main component of the battery current collector 10, and serves as a conductive path between the electrode active material layer 5 and the battery terminal. The conductor layer 2 is, for example, a metal foil, more specifically, an aluminum foil, a copper foil, a stainless steel foil, a nickel foil, etc. The conductor layer 2 may be subjected to a corona discharge treatment before forming the primer layer 3. Thus, the hydrophilicity of the surface of the conductor layer 2 can be improved, and an aqueous dispersion medium can be used in the formation of the primer layer 3.
[0030] The primer layer 3 is a layer provided on the conductor layer 2. In the battery electrode 20, the primer layer 3 is located between the conductor layer 2 and the electrode active material layer 5. The primer layer 3 serves as a binder to bond the conductor layer 2 and the electrode active material layer 5, and can suppress the electrode active material layer 5 from peeling off from the conductor layer 2 during the charge and discharge of the battery.
[0031] The primer layer 3 is a layer of dispersed crystalline resin. Figure 1In the current collector 10 shown in (a), the undercoat layer 3 is a layer in which a plurality of crystalline resin particles 4 are dispersed. Therefore, the conductor layer 2 is exposed in the gaps between the plurality of crystalline resin particles 4. By making the undercoat layer 3 have such a structure, in the battery electrode 20, the conductor layer 2 and the electrode active material layer 5 can be in contact in the gaps, and the internal resistance of the battery electrode 20 can be suppressed from increasing.
[0032] The crystalline resin (crystalline polymer) contained in the primer layer 3 is a polymer with crystallinity and has a glass transition temperature and a melting point. In addition, the melting point of the crystalline resin contained in the primer layer 3 is below 200°C. Thus, when the useful components contained in the used battery electrode 20 are reused, the crystalline resin is melted by heating at least a portion of the primer layer 3 to a temperature above the melting point of the crystalline resin, which can weaken the bonding between the primer layer 3 and the conductor layer 2 or the bonding between the primer layer 3 and the electrode active material layer 5, and the electrode active material layer 5 can be easily peeled off from the conductor layer 2. In addition, the melting point of the crystalline resin contained in the primer layer 3 can be below 180°C or below 160°C.
[0033] The crystalline resin contained in the primer layer 3 is, for example, polyolefin, specifically, polyethylene, polypropylene, ethylene-propylene copolymer, etc. Alternatively, the primer layer 3 may include a mixture of at least two of these resins.
[0034] The plurality of crystalline resin particles 4 contained in the primer layer 3 may have an average particle size D50 of 0.1 μm or more and 40 μm or less, preferably 0.1 μm or more and 30 μm or less, and more preferably 0.1 μm or more and 20 μm or less. Thus, the internal resistance of the battery electrode 20 can be suppressed from increasing, and the electrode active material layer 5 can be suppressed from peeling off from the conductor layer 2 during the charge and discharge of the battery.
[0035] The mass of the primer layer 3 per unit area is, for example, 0.1 g / m 2 Above and less than 10g / m 2 , preferably 0.3g / m 2 Above and 9g / m 2 As a result, it is possible to suppress the internal resistance of the battery electrode 20 from increasing, and to suppress the electrode active material layer 5 from being peeled off from the conductor layer 2 during charge and discharge of the battery.
[0036] The undercoat layer 3 can be formed, for example, by applying a dispersion (coating solution) in which the crystalline resin particles 4 are dispersed in an aqueous dispersion medium onto the conductor layer 2 and drying the coating film. The method for applying the coating solution for the undercoat layer onto the conductor layer 2 is not particularly limited, and for example, a gravure coating method is used.
[0037] In addition, the coating film of the undercoat layer coating liquid can be dried at a temperature not higher than the melting point of the crystalline resin particles 4 .
[0038] The coating liquid (dispersion liquid) for the base coat layer may contain a water-soluble organic compound or a liquid organic compound. Thus, the crystalline resin particles 4 can be suppressed from agglomerating, and the homogeneity of the base coat layer 3 can be improved. The water-soluble organic compound or the liquid organic compound, for example, isopropyl alcohol, dipropylene glycol monomethyl ether, diethylene glycol monomethyl ether, methylcyclohexane, ethyl acetate, N-methyl-2-pyrrolidone (NMP), cyclohexanone, tetralin, n-dodecane, etc. The coating liquid for the base coat layer may contain two or more of these organic compounds.
[0039] The ratio of the organic compound in the undercoat layer coating liquid is, for example, 0.5 mass % to 85 mass %, preferably 0.5 mass % to 55 mass %, and more preferably 1.0 mass % to 35 mass %.
[0040] The electrode active material layer 5 formed on the undercoat layer 3 may be a positive electrode active material layer or a negative electrode active material layer. The electrode active material layer 5 may be porous and may contain electrode active material particles and a binder. In addition, the electrode active material layer 5 may contain a conductive material as required.
[0041] The electrode active material layer 5 may be a layer obtained by drying a coating film formed by applying an electrode active material layer paste, or may be a layer obtained by attaching a thin film containing an electrode active material to a battery current collector 10 (for example, a battery electrode produced by a dry process, an all-solid-state battery electrode, etc.).
[0042] In addition, in the battery electrode 20 having the electrode active material layer 5 on the battery current collector 10 having an undercoat layer formed using an undercoat coating liquid containing a water-soluble organic compound or a liquid organic compound, the electrode active material layer 5 has high adhesion to the battery current collector 10.
[0043] In the case of a positive electrode of a lithium ion battery, the electrode active material is, for example, lithium nickel cobalt manganese oxide, lithium iron phosphate, etc. The average particle size of the electrode active material particles is, for example, 0.1 μm or more and 50 μm or less.
[0044] Second embodiment
[0045] Figure 1 (b) is a schematic cross-sectional view of a battery current collector according to this embodiment, Figure 2 (b) is a schematic cross-sectional view of the battery electrode according to this embodiment.
[0046] The battery current collector 10 of this embodiment comprises a conductor layer 2 and an undercoat layer 3 provided on the conductor layer 2. The undercoat layer 3 is a mixture layer of a crystalline resin and carbon particles. The mass of the undercoat layer 3 per unit area is 0.1 g / m 2 Above and less than 10g / m 2 , the melting point of the crystalline resin contained in the primer layer 3 is 200° C. or less.
[0047] Since the conductor layer 2 has been described in the first embodiment, its description is omitted here.
[0048] The undercoat layer 3 is a layer provided on the conductive layer 2. In the battery electrode 20, the undercoat layer 3 is located between the conductive layer 2 and the electrode active material layer 5.
[0049] The undercoat layer 3 is a mixture layer of a crystalline resin having a melting point of 200° C. or less and carbon particles. The carbon particles contained in the undercoat layer 3 serve as a conductive path between the conductor layer 2 and the electrode active material layer 5. Therefore, it is possible to suppress the increase in resistance between the conductor layer 2 and the electrode active material layer 5. In addition, the undercoat layer 3 can also have the function of protecting the conductor layer 2 from the influence of the electrolyte.
[0050] The carbon particles contained in the primer layer 3 are, for example, conductive materials such as graphite particles, carbon black, carbon nanotubes, graphene, and mixtures of two or more thereof. The average particle size D50 of the carbon particles contained in the primer layer 3 is, for example, 50 μm or less, preferably 30 μm or less, and more preferably 20 μm or less.
[0051] The crystalline resin (crystalline polymer) contained in the primer layer 3 has a function as a binder of the primer layer 3. The crystalline resin has been described in the first embodiment and is omitted here. In addition, the size or thickness of the crystalline resin in the primer layer 3 is greater than 0.1 μm and less than 40 μm, preferably greater than 0.1 μm and less than 30 μm, and more preferably greater than 0.1 μm and less than 20 μm.
[0052] The primer layer 3 can contain 0.01 to 1000 parts by mass of carbon particles, preferably 0.1 to 800 parts by mass of carbon particles, and more preferably 1 to 500 parts by mass of carbon particles, relative to 100 parts by mass of the crystalline resin. By making the primer layer 3 contain carbon particles, the internal resistance of the battery electrode 20 can be suppressed from becoming high.
[0053] The mass of the primer layer 3 per unit area (unit area weight) is 0.1 g / m 2 Above and 10g / m 2 Below, preferably 0.3g / m 2 Above and 7.0g / m2 Below, preferably 0.5g / m 2 Above and 5.0g / m 2 By making the mass of the primer layer 3 0.1 g / m 2 As described above, when the electrode active material layer 5 is peeled off from the conductor layer 2 by the peeling method described later, it is possible to suppress a portion of the electrode active material layer 5 from remaining on the conductor layer 2. 2 Next, the amount of the electrode active material layer 5 in the electrode can be increased.
[0054] The primer layer 3 may be a layer having a substantially uniform thickness.
[0055] The primer layer 3 can be set so that all the carbon particles contained in the primer layer 3 are not covered by the crystalline resin. Thus, the resistance of the primer layer 3 can be suppressed from becoming high. For example, by applying a primer coating liquid mixed with an aqueous dispersion medium, carbon particles and crystalline resin particles on the conductor layer 2 and drying the coating film, such a primer layer 3 can be formed. In other words, since the crystalline resin is almost insoluble in the aqueous dispersion medium, it is possible to suppress all the carbon particles from being covered by the crystalline resin. The coating method and the drying of the coating film are omitted here because they have been described in the first embodiment.
[0056] In addition, the electrode active material layer 5 and the electrode active material have also been described in the first embodiment, and thus their description is omitted here.
[0057] The description in the first embodiment is also the same as for the second embodiment unless there is any contradiction.
[0058] Third embodiment
[0059] The present embodiment provides a stripping method for stripping the electrode active material layer 5 contained in the electrode 20 from the conductor layer 2. The stripping method of the present embodiment includes a stripping step of heating at least a portion of the primer layer 3 contained in the electrode 20 to a temperature higher than the melting point of the crystalline resin to strip the electrode active material layer 5 from the conductor layer 2.
[0060] In the peeling step, the electrode active material layer 5 can be peeled from the conductor layer 2 while the temperature of the primer layer 3 is at least the melting point of the crystalline resin. In this state, the electrode active material layer 5 can be easily peeled from the conductor layer 2 because the crystalline resin is melted.
[0061] In addition, in the stripping step, at least a portion of the undercoat layer 3 contained in the electrode 20 may be heated to a temperature above the melting point of the crystalline resin (heat treatment), and then after the temperature of the undercoat layer 3 becomes lower than the temperature of the crystalline resin, the electrode active material layer 5 may be stripped from the conductor layer 2. In this case, the crystalline resin contained in the undercoat layer 3 is melted by the heat treatment, thereby reducing the bonding between the undercoat layer 3 and the conductor layer 2 or the bonding between the undercoat layer 3 and the electrode active material layer 5, and the electrode active material layer 5 can be easily stripped from the conductor layer 2.
[0062] The stripping step may also include heating the electrode 20 for 0.5 seconds to 20 seconds using a furnace, a heating plate, or a heating roller at a temperature of 100° C. to 300° C. (a temperature higher than the melting point of the crystalline resin). In this way, the crystalline resin contained in the primer layer 3 can be melted, thereby reducing the bonding between the primer layer 3 and the conductor layer 2 or the bonding between the primer layer 3 and the electrode active material layer 5.
[0063] The stripping step may also include a step of heating the primer layer 3 from the side of the conductor layer 2. Thus, the bonding between the primer layer 3 and the conductor layer 2 can be reduced. For example, the electrode 20 may be heated from the side of the conductor layer 2 using a heating plate, or the electrode 20 may be heated from the side of the conductor layer 2 using a heating roller. In addition, in the case where the primer layer 3 and the electrode active material layer 5 are respectively provided on both surfaces of the collector 10, the primer layer 3 may be heated via the conductor layer 2 by heating a portion of the conductor layer 2 where the primer layer 3 and the electrode active material layer 5 are not provided.
[0064] Lithium-ion battery manufacturing
[0065] Lithium ion batteries of Examples 1 to 4 and Comparative Examples 1 to 4 were prepared. Table 1 shows the amount of polyethylene (PE) contained in the primer layer of the positive electrode contained in the lithium ion battery and the mass of the primer layer per unit area (weight per unit area). In addition, Table 1 also shows the amount of carbon particles contained in the primer layer of the positive electrode contained in each lithium ion battery of Examples 3 and 4 and Comparative Examples 2 to 4.
[0066] Table 1
[0067]
[0068] [Example 1]
[0069] Water and polyethylene particles (average particle size: about 10 μm) were mixed to prepare a primer coating. The primer coating was applied to a corona discharge treated aluminum foil by gravure coating so that the mass of the primer per unit area (unit area weight) was 6.4 g / m 2Then, the coating film is dried to form a primer layer. In Example 1, since the primer layer is formed using polyethylene particles, the primer layer can be considered to be a layer in which polyethylene particles are dispersed.
[0070] A positive electrode active material paste was prepared by mixing lithium nickel cobalt manganese oxide (ternary system NCM811, average particle size 10 μm) as a positive electrode active material, a binder and a solvent, and the positive electrode active material paste was applied to the undercoat layer and dried to form a positive electrode active material layer. In this way, the positive electrode for the battery of Example 1 was prepared.
[0071] A negative electrode active material paste was prepared by mixing graphite particles as a negative electrode active material and an aqueous dispersion medium, and the negative electrode active material paste was applied on a copper foil and dried to form a negative electrode active material layer. In this way, a negative electrode for a battery was produced.
[0072] A coin-type lithium ion battery of Example 1 was produced using the produced battery positive electrode, battery negative electrode, separator, and electrolyte.
[0073] [Example 2]
[0074] In forming the primer layer, the primer coating material was applied on the aluminum foil treated with corona discharge by gravure coating so that the mass of the primer layer per unit area (unit area weight) was 1.0 g / m 2 , except for this, a positive electrode for battery and a lithium ion battery of Example 2 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Example 2, since the primer layer was made of polyethylene particles, the primer layer can be considered to be a layer in which polyethylene particles are dispersed.
[0075] [Example 3]
[0076] A primer coating material is prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 33 parts by mass of carbon particles (graphite particles + carbon black) and an aqueous dispersion medium; and in forming the primer coating material, the primer coating material is applied on an aluminum foil treated with corona discharge by using a gravure coating method so that the mass of the primer coating material per unit area (unit area weight) is 1.5 g / m 2 , except for this, the positive electrode for battery and the lithium ion battery of Example 3 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Example 3, since the undercoat layer was made of polyethylene particles and carbon particles, it can be considered that the undercoat layer is a mixture layer of polyethylene particles and carbon particles.
[0077] [Example 4]
[0078] The primer coating material is prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 20 parts by mass of carbon particles (graphite particles + carbon black) and an aqueous dispersion medium; and in the formation of the primer coating material, the primer coating material is applied on an aluminum foil treated with corona discharge by using a gravure coating method so that the mass of the primer coating per unit area (unit area weight) is 1.0 g / m 2 , except for this, the positive electrode for battery and the lithium ion battery of Example 4 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Example 4, since the undercoat layer was made of polyethylene particles and carbon particles, it can be considered that the undercoat layer is a mixture layer of polyethylene particles and carbon particles.
[0079] [Comparative Example 1]
[0080] In forming the primer layer, the primer coating material was applied on the aluminum foil treated with corona discharge by gravure coating so that the mass of the primer layer per unit area (unit area weight) was 10.0 g / m 2 , except for this, the positive electrode for battery and the lithium ion battery of Comparative Example 1 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Comparative Example 1, since the primer layer was made of polyethylene particles, the primer layer can be considered to be a layer of polyethylene particles, but since the mass of the primer layer per unit area is large, it can be considered that the density of the polyethylene particles becomes high.
[0081] [Comparative Example 2]
[0082] The primer coating material is prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 50 parts by mass of carbon particles (graphite particles + carbon black) and an aqueous dispersion medium; and in the formation of the primer coating material, the primer coating material is applied on an aluminum foil treated with corona discharge by using a gravure coating method so that the mass of the primer coating per unit area (unit area weight) is 0.4 g / m 2 , except for this, the positive electrode for battery and the lithium ion battery of Comparative Example 2 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Comparative Example 2, since the primer layer was made of polyethylene particles and carbon particles, it can be considered that the primer layer is a mixture layer of polyethylene particles and carbon particles.
[0083] [Comparative Example 3]
[0084] 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 33 parts by mass of carbon particles (graphite particles + carbon black) and an aqueous dispersion medium are mixed to prepare a primer coating material; and in the formation of the primer coating material, the primer coating material is applied on an aluminum foil treated with corona discharge by using a gravure coating method so that the mass of the primer coating material per unit area (unit area weight) is 0.2 g / m 2, except for this, the positive electrode for battery and the lithium ion battery of Comparative Example 3 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Comparative Example 3, since the undercoat layer was made of polyethylene particles and carbon particles, it can be considered that the undercoat layer is a mixture layer of polyethylene particles and carbon particles.
[0085] [Comparative Example 4]
[0086] A primer coating material is prepared by mixing 100 parts by mass of polyethylene particles (average particle size: about 10 μm), 20 parts by mass of carbon particles (graphite particles + carbon black) and an aqueous dispersion medium; and in forming the primer coating material, the primer coating material is applied on an aluminum foil treated with corona discharge by using a gravure coating method so that the mass of the primer coating material per unit area (unit area weight) is 10.5 g / m 2 , except for this, the positive electrode for battery and the lithium ion battery of Comparative Example 4 were prepared in the same manner as the positive electrode for battery and the lithium ion battery of Example 1. In Comparative Example 4, since the undercoat layer was made of polyethylene particles and carbon particles, it is considered that the undercoat layer is a mixture layer of polyethylene particles and carbon particles.
[0087] Charge and discharge cycle test
[0088] Each lithium ion battery of Examples 1 to 4 and Comparative Examples 1 to 4 was used to perform 100 charge and discharge cycles, and then the charge and discharge cycle characteristics of each lithium ion battery were evaluated. The evaluation results are shown in Table 1. In Table 1, the evaluation of lithium ion batteries with a charge and discharge efficiency of 80% or more at the 100th cycle is indicated by "0", and the evaluation of lithium ion batteries with a charge and discharge efficiency of 80% or less at the 100th cycle is indicated by "×".
[0089] The lithium ion batteries of Examples 1 to 4 and Comparative Examples 2 and 3 were evaluated as "○", and it was found that these batteries had high charge and discharge efficiency.
[0090] The evaluation of the lithium ion battery of Comparative Example 1 was “×”. This is considered to be because the mass of the undercoat layer per unit area was large and the density of the polyethylene particles was high, so the internal resistance of the positive electrode increased.
[0091] The lithium ion battery of Comparative Example 4 was evaluated as “×”. This is considered to be because the internal resistance of the positive electrode increased due to the increase in the mass per unit area of the undercoat layer.
[0092] Peel test
[0093] After 100 charge and discharge cycles, each lithium-ion battery of Examples 1 to 4 and Comparative Examples 1 to 4 was disassembled, the positive electrode was removed from the battery, and the electrolyte attached to the positive electrode was wiped clean. Then, an adhesive tape was attached to a portion of the positive electrode active material layer of the positive electrode, and a 100 g weight was placed on the adhesive tape. The adhesive tape was repeatedly applied with a load three times to firmly attach the adhesive tape to the positive electrode active material layer. Then, the adhesive tape was peeled off from the aluminum foil. Then, the aluminum foil and the adhesive tape were observed to evaluate whether the positive electrode active material layer was peeled off from the aluminum foil (evaluation of "no heat treatment").
[0094] In addition, each positive electrode taken out from each lithium ion battery of Examples 1 to 4 and Comparative Examples 1 to 4 after 100 charge and discharge cycles was heated on a heating plate at 200°C for about 5 seconds (heat treatment). After the heat treatment, an adhesive tape was attached to a portion of the positive electrode active material layer whose temperature had sufficiently dropped, and a 100g weight was placed on the adhesive tape. The load was applied to the adhesive tape three times, and the adhesive tape was firmly attached to the positive electrode active material layer. Then, the adhesive tape was peeled off from the aluminum foil. Then, the aluminum foil and the adhesive tape were observed to evaluate whether the positive electrode active material layer was peeled off from the aluminum foil (evaluation of "heat treatment").
[0095] The evaluation of "without heat treatment" and the evaluation of "with heat treatment" are shown in Table 1. In Table 1, the evaluation of the positive electrode in which almost all of the positive electrode active material layer is peeled off from the aluminum foil together with the undercoat layer is shown as "◎", the evaluation of the positive electrode in which almost all of the positive electrode active material layer is peeled off from the aluminum foil separately from the undercoat layer is shown as "○", the evaluation of the positive electrode in which a part of the positive electrode active material layer remains on the aluminum foil is shown as "△", and the evaluation of the positive electrode in which almost all of the positive electrode active material layer remains on the aluminum foil is shown as "×".
[0096] The evaluation of the peeling test of the positive electrode of Examples 1 and 2 without heat treatment (evaluation without heat treatment) is "△", while the evaluation of the peeling test of the positive electrode of Examples 1 and 2 with heat treatment (evaluation with heat treatment) is "0" or "◎". Therefore, it can be seen that in these positive electrodes, the positive electrode active material layer is easily peeled off from the aluminum foil by heat treatment. Therefore, it can be seen that the positive electrode has a primer layer in which polyethylene particles are dispersed, and the positive electrode active material layer can be easily peeled off from the aluminum foil by heat treatment.
[0097] The evaluation of the peeling test of the positive electrode of Examples 3 and 4 without heat treatment (evaluation without heat treatment) is "△", while the evaluation of the peeling test of the positive electrode of Examples 3 and 4 with heat treatment (evaluation with heat treatment) is "0". Therefore, it can be seen that in these positive electrodes, the positive electrode active material layer is easily peeled off from the aluminum foil by heat treatment. Therefore, it can be seen that the positive electrode has an undercoat layer of a mixture layer of polyethylene and carbon particles, and the positive electrode active material layer can be easily peeled off from the aluminum foil by heat treatment.
[0098] The evaluation of the peel test of the positive electrode of Comparative Example 1 which was not subjected to heat treatment (evaluation without heat treatment) was "◎", and the evaluation of the peel test of the positive electrode of Comparative Example 1 which was subjected to heat treatment (evaluation with heat treatment) was "◎". In the positive electrode of Comparative Example 1, it is believed that the evaluation of the peel test was also high because the density of the polyethylene particles in the primer layer was high.
[0099] The evaluation of the peel test of the positive electrode of Comparative Examples 2 and 3 in which the heat treatment was not performed (evaluation without heat treatment) and the evaluation of the peel test of the positive electrode of Comparative Examples 2 and 3 in which the heat treatment was performed (evaluation with heat treatment) were both "×". In the positive electrodes of Comparative Examples 2 and 3, it is considered that the mass of the primer layer per unit area is small, so the evaluation of the peel test becomes low.
[0100] The evaluation of the peel test of the positive electrode of Comparative Example 4, which was not subjected to heat treatment (evaluation without heat treatment), was "0", and the evaluation of the peel test of the positive electrode of Comparative Example 4, which was subjected to heat treatment (evaluation with heat treatment), was "◎". In the positive electrode of Comparative Example 4, it is believed that the evaluation of the peel test became high because the polyethylene content of the primer layer was high and the mass of the primer layer per unit area was large.
[0101] SEM observation
[0102] SEM observation of the cross section of the positive electrode of Example 3 after heat treatment. The SEM photograph is shown in Figure 3 .Depend on Figure 3 It can be seen from the photograph that a gap is formed between the aluminum foil and the positive electrode active material layer. The gap is believed to be formed by melting the polyethylene contained in the primer layer by heat treatment, thereby peeling the primer layer from the aluminum foil. In the positive electrodes of Examples 1 to 4 after heat treatment, since such a gap is formed by heat treatment, it can be considered that the positive electrode active material layer becomes easy to peel off from the aluminum foil.
Claims
1. A battery current collector, characterized in that: It comprises a conductive layer and a primer layer provided on the conductive layer, wherein: The undercoat layer is a layer of dispersed crystalline resin or a mixture layer of crystalline resin and carbon particles; When the undercoat layer is a layer of the dispersed crystalline resin, the conductive layer is exposed in the gaps of the crystalline resin contained in the undercoat layer; when the undercoat layer is a mixture layer of the crystalline resin and carbon particles, the mass of the undercoat layer per unit area is 0.1 g / m 2 Above and less than 10g / m 2 ; The melting point of the crystalline resin contained in the primer layer is 200° C. or lower.
2. The battery current collector according to claim 1, wherein The undercoat layer is the mixture layer of the crystalline resin and the carbon particles, and contains 0.01 parts by mass or more and 1000 parts by mass or less of the carbon particles relative to 100 parts by mass of the crystalline resin.
3. The battery current collector according to claim 1, wherein The primer layer is a layer of the dispersed crystalline resin, and is a layer in which crystalline resin particles having an average particle size D50 of 0.1 μm or more and 40 μm or less are dispersed, and the mass of the primer layer per unit area is 0.1 g / m 2 Above and less than 10g / m 2 .
4. The battery current collector according to claim 1, wherein The undercoat layer is a mixture layer of a crystalline resin and carbon particles, the size or thickness of the crystalline resin in the undercoat layer is 40 μm or less, and the mass of the undercoat layer per unit area is 0.1 g / m 2 Above and 10g / m 2 the following.
5. The battery current collector according to claim 4, wherein The undercoat layer is provided so that all carbon particles are not covered with the crystalline resin.
6. The battery current collector according to claim 1, wherein The conductor layer is a metal foil.
7. The battery current collector according to claim 1, wherein The crystalline resin contained in the primer layer is a polyolefin. 8 . A battery electrode, comprising the current collector according to claim 1 and an electrode active material layer provided on the undercoat layer.
9. A method for preparing a collector for a battery, the method comprising the steps of: applying a dispersion containing crystalline resin particles dispersed in a dispersion medium comprising a water-soluble organic compound or a liquid organic compound and water onto a conductive layer, and drying the coating film to form a primer layer.
10. A stripping method for stripping an electrode active material layer contained in an electrode from a conductive layer, wherein the electrode comprises a current collector and an electrode active material layer, the current collector comprises a conductive layer and an undercoat layer provided on the conductive layer, the electrode active material layer being provided on the undercoat layer, in, The undercoat layer is a dispersed crystalline resin layer or a mixture layer of a crystalline resin and carbon particles; The melting point of the crystalline resin contained in the primer layer is 200° C. or less; The peeling method includes a peeling step of heating at least a portion of the undercoat layer to a temperature equal to or higher than a melting point of the crystalline resin to peel the electrode active material layer from the conductor layer.
11. The stripping method according to claim 10, wherein: The peeling step includes heating the electrode for a period of time of 0.5 seconds to 20 seconds using a furnace, a heating plate, or a heating roller at a temperature of 100° C. to 300° C. inclusive.
